Moralitas dan Etika Konsumsi VS Gaya Hidup Anak Muda dalam Tren “Buy Now Pay Later” - PURWANTI, TARI; Azhar, Fadhilatul; Suyanto, Suyanto (Umbara, 2026)
This study explores how moral values, social pressures, and digital culture shape young people's consumption behavior through PayLater services in Indonesia. Using a qualitative descriptive approach with a netnographic method, the research analyzed 29 social media posts from X (formerly Twitter) containing narratives related to experiences, moral justification, and emotions surrounding PayLater use. The findings reveal that PayLater is not merely a financial tool but a medium of social participation and symbolic identity formation. Young users often justify their indebtedness as acts of self-care, reward, or emotional recovery, reflecting a flexible moral framework shaped by digital narratives. Moreover, social validation and Fear of Missing Out (FOMO) drive individuals to engage in consumption as a form of belonging. Humor, memes, and viral hashtags such as #PaylaterWarrior play a crucial role in normalizing debt-based consumption, transforming financial anxiety into collective cultural expression. Thus, the PayLater phenomenon illustrates how debt becomes moralized, aestheticized, and socially legitimate within the digital youth culture.